Lotass och läsmaskinen: Om läsningens mekanismer i Lotta Lotass Fjärrskrift - Ljungström, Linus (Tidskrift för litteraturvetenskap, 2016)
Lotass and the Reading Machine: on Reading Mechanisms in Lotta Lotass’ Fjärrskrift. The American modernist Bob Brown (1886–1959) had a vision of modernising the way we read by moving away from the traditional book medium. He proposed a reading machine to revolutionise the literary experience, in the same manner that the ”talkies” revolutionised the experience of film. In her work Fjärrskrift (”Distant Writing” or ”Teleprinter”) Lotta Lotass (1964–) creates a reading experience which resembles Brown’s vision. Fjärrskrift is a work that makes use of three different media – a 50-meter-long teleprinter strip, and two filmed versions distributed in cinemas and published online – portraying how the strip is made through a teleprinter. Utilising Lars Elleström’s theory of intermediality, this article investigates various connections between the three different media versions of Fjärrskrift and how the work distances itself from the traditional book medium. Most prominently, the article questions the effect the medial implications have on the reading process, and the mechanisms attached to it. I conclude that Fjärrskrift, rather than offering a revolutionary alternative to the book medium, creates an uncomfortable reading experience that put focus on the process of reading as such.